2019
DOI: 10.18267/j.cebr.203
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Tourism Experience Co-Creation, Life Satisfaction and Behavioural Intentions

Abstract: This paper contributes to the debate about the relationships among tourism experience cocreation, satisfaction with vacation experience, satisfaction with the impact of vacation on overall life, life satisfaction and behavioral intentions. The main purpose of this paper is to point out the importance of tourist engagement in the co-creation of the vacation experience and the impact of satisfaction with that experience on life satisfaction and behavioral intentions. A survey was conducted on a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In terms of adventure tourism, Paul and Geoffrey N. (2009) researched the significance of value on satisfaction and behavioral intentions and conceptualized values as value for money, emotional value, and novelty value [36]. The structural research of experience/perception (value), satisfaction, and behavior intentions are becoming an increasing tendency in terms of ecotourism and leisure tourism [37,38].…”
Section: Experience Value Satisfaction and Revisit Intentionsmentioning
confidence: 99%
“…In terms of adventure tourism, Paul and Geoffrey N. (2009) researched the significance of value on satisfaction and behavioral intentions and conceptualized values as value for money, emotional value, and novelty value [36]. The structural research of experience/perception (value), satisfaction, and behavior intentions are becoming an increasing tendency in terms of ecotourism and leisure tourism [37,38].…”
Section: Experience Value Satisfaction and Revisit Intentionsmentioning
confidence: 99%
“…Destination image (Souiden et al, 2017;Prayag and Ryan, 2012;Satyarini, Rahmanita and Setarnawat, 2017) and destination attachment (Song, Kim and Yim, 2017;Sohn and Yoon, 2016;Yuskel et al, 2010;Chen et al, 2013) were found to be of significance on a tourist plan to visit (Kim et al, 2020). Destination satisfaction was also found to be a significat mediator in the above stated relationships (Lončarić, Prodan and Bagarić, 2018;Wang and Hsu, 2010). Therefore, Pakistan must place more emphasis in providing an unforgettable experience to the tourists with the aim that repeat visitations can be guaranteed.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 97%
“…Destination satisfaction is a critical issue in deciding the visitor's decision to return to a destination (Chen and Tsai, 2007;Chi and Qu, 2008). Research have been led to discover the connection among destination satisfaction and destination image (Bigne et al, 2001;Lončarić, Prodan and Bagarić, 2018), for the most part studies have observed the immediate relationship to be direct (Wang and Hsu, 2010). In some studies, a negative relationship has been also seen (Del et al, 2008).…”
Section: Destination Familiaritymentioning
confidence: 99%
“…Tourism co-creation is considered as the total psychological events that a tourist goes through when actively participating in activities and engaging with other people in the experience environment (Campos et al, 2018). Co-creation of the tourism experience significantly contributes to tourists' satisfaction while staying in a destination, which has a favorable impact on life satisfaction and future behavioral intentions (Loncˇaric´et al, 2019). The advantages of value and experience co-creation are linked to organizations' and tourists' ability to collaborate to enhance their satisfaction and expectations (Dı´az et al, 2023).…”
Section: Smart Infrastructure Co-creation and Tourists' Experiencesmentioning
confidence: 99%